Modified Atkins ketogenic diet improves heart and skeletal muscle function in glycogen storage disease type III - FRANCINI-PESENTI, FRANCESCO (Acta Myol, 2019)
Glycogen storage disease type III (GSDIII) management in adult patients includes a high-protein diet with cornstarch supplementation to maintain a normal level of glucose in the blood. This regimen can prevent hypoglycaemia but does not seem to improve skeletal muscle and heart function. A 34 years-old patient with GSD IIIa with hypertrophic cardiomyopathy was then treated with a modified Atkins ketogenic diet. After 12 months of treatment ejection fraction raised from 30 to 45%, liver enzymes were reduced and CK plasma level dropped from 568 to 327 U/l. Physical activity increased from about 1300 to 2800 steps per day and health-related quality of life assessment ameliorated. An increase in uric acid triglycerides plasma level was observed. This data obtained in an adult patient confirm previous reports evidencing the effectiveness of ketogenic diets in improving cardiac and muscular manifestations in children with GSDIII.